A CASE OF SUDDEN CARDIORESPIRATORY ARREST IN LATERAL MEDULLARY SYNDROME - K SLEEBA, SHIJU; MUSTHAFA AK, MOHAMMED; KP, DIPU; PA, KABEER (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Sudden cardiorespiratory arrest can occur several days after lateral medullary infarction especially when the patients were both medically and neurologically stable after a stroke which caused only minimal motor disability. Cardiac arrhythmia is among one of the mechanisms by which cardiorespiratory arrest have occurred. Another cause is that the lateral medullary infarction and surrounding brain tissue (possibly ischemic penumbra) may have affected the brain stem cardiac and respiratory centers together with autonomic pathways. Medullary lesions can cause autonomic instability which can precipitate death in each case. It is plausible that ischemic lesions of the solitary tract nuclei result initially with some lateral medullary infarctions, and that such lesions may in turn precipitate some occurrences of cardiorespiratory arrest. 54-years-old male presented with difficulty in swallowing, hoarseness of voice, vomiting, difficulty in walking and sitting upright. On the evaluation, he had left sided central facial nerve palsy, paralysis of the left soft palate, dysphagia, decreased pain and temperature sensation over the left face and upper limb, and cerebellar signs (dysdiadochokinesia and past pointing) in the left upper limb and truncal ataxia. Magnetic resonance imaging disclosed high intensity area in the left lateral and dorso-medial medulla in T2-weighted image. He developed rapidly progressive respiratory failure followed by sudden cardiorespiratory arrest. He was resuscitated and put on mechanical ventilation. He further developed severe hypotension not responding to intravenous inotropic supports. On 3rd day of hospital stay, he developed sudden cardiac arrest. Autonomic instability and sudden cardiorespiratory arrest which are rare manifestations of lateral medullary syndrome have occurred together in this patient. Keywords: India, Kerala, Kottakkal, lateral medullary syndrome, Malappuram, Ondine's curse, sudden cardiorespiratory arrest